Prevalence of hypothyroidism, diabetes mellitus and delayed puberty in patients of thalassemia major in a tertiary care center of Jammu province, Jammu Kashmir, India - Sharma, Sushil; Dutt, Neeti; Sidhu, Meena; Digra, Sanjeev; Meenia, Renu (International Journal of Advances in Medicine, 2017)
Background: Thalassemia is a common genetic disorder which is associated with a lot of complications. Frequent blood transfusions result in increased iron deposition in various tissues leading to dysfunction of many organs of our body. Endocrine disorders constitute a major part of such complications increasing the morbidity of thalassemia manifold in the affected patients. Methods: This is a prospective study carried out in 64 thalassemia major patients attending thalassemia day care centre at SMGS Hospital Jammu from December 2014 to November 2015. Patients were examined and investigated for presence of one or more endocrine disorders including diabetes mellitus, hypothyroidism and delayed puberty. Results: Endocrine disorders were detected in a total of 22 patients. Diabetes mellitus was detected in 4.7% (n=3) patients, hypothyroidism in 4.7% (n=3) patients and delayed puberty was found in 26.6% (n=17) patients. Mean serum ferritin level was found to be 2885.5 ng/ml and there was no significant difference in patients affected with endocrine disorder and those without any endocrine disorder. Conclusions: Endocrine complications occur commonly in patients of thalassemia major. Increasing life span of thalassemia patients has increased the number of patients living with these disorders. A lot of morbidity occurs due to the presence of one or more of these disorders. Hence timely detection of these disorders by screening in all patients of thalassemia should be done to initiate treatment at the earliest so as to limit the morbidity caused by these disorders.